Ewolucja Stereotypu Matki Polki - Szlachta-Ignatowicz, Justyna (Przegląd Środkowo-Wschodni, 2022)
The article deals with the evolution of the stereotype / myth of the Polish Mother. The starting point for the considerations were two sociological and statistical books, and the inspiration was the newest book by Anna Dziewit-Meller. During the considerations, a specific classification of the category of the Polish Mother was created, which shows the evolution of the stereotype / myth in question. In the next part, considerations concerning the very image of the Mother of Poland were discussed, inter alia, from the point of view of men and women as well as inhabitants of the countryside and the city.